A Five-Year Study Comparing the Millard and Tennison Technique for Unilateral Cleft Lip Repair (Razi Medical Journal, 2025)
Healing from unilateral cleft lip surgically corrects one of the most common congenital craniofacial disorders, which impacts the face, oral function, and mental wellness in depth. While scarring is inevitable after surgery, it should also be minimal to provide a natural appearance while restoring symmetry and lip contours. This study aims to compare the Tennison-Randall triangular flap method and the Millard rotation-advancement technique in the surgical treatment of infants with unilateral cleft lip over five years. The Millard and Tennison groups each received 60 patients, ranging in age from three to six months. The surgeries were performed at the National Cancer Institute, Misrata-Libya. Clinical outcomes were assessed using the Manchester Scar Scale, photometric analysis for lip symmetry, nasal anthropometry for nasal base configuration, and subjective parental satisfaction surveys. The Millard technique demonstrated significantly better results in lip symmetry (p = 0.02), scar quality (p = 0.03), and parental satisfaction (87%), when compared to the Tennison group (78%). Using the Tennison method, the nasal base symmetry was slightly improved (p = 0.07), although this difference was not statistically significant. Both techniques are reliable for repairing a unilateral cleft lip. The Millard method is the preferred choice in clinical practice for its better functional and aesthetic outcomes.
Keywords: Millard and Tennison Technique, Cleft Lip, Craniofacial Disorders.